PEMBERDAYAAN EKONOMI MASYARAKAT BERBASIS PARIWISATA PERSPEKTIF EKONOMI ISLAM: (Studi Pada Pengrajin Gerabah di Desa Banyumulek Kabupaten Lombok Barat NTB - Muh Zidni syukran (TAFAQQUH: Jurnal Hukum Ekonomi Syariah Dan Ahwal Syahsiyah, 2019)
This study aimed (1) to describe the existing economic empowerment for a tourism-based community from the perspective of Islamic economy and the community’s efforts to develop entrepreneurship in Banyumulek Village, a tourist destination for pottery handicrafts, from the perspective of Islamic economy, by establishing a CBT (community-based tourism) in Banyumulek Village, Kediri District, Lombok Barat Regency, NTB, (2) to identify the tourism potential to be developed into a CBT in Banyumulek Village, (3) to describe the forms of economic empowerment suitable for tourism-based community in Banyumulek Village, and (4) to formulate a model of CBT development as a strategy for community’s economic empowerment in Banyumulek Village. This research used the descriptive-qualitative design. The researcher became the active instrument in the efforts to collect data from the field. Data was obtained from the Office of Cooperatives and Trade, the local administrators of Banyumulek Village, Women’s Cooperative of Pottery Craftsmen (KOPWAN), and the craftsmen in Banyumulek Village. The techniques for data gathering included interview, observation, and documentation. Data analysis was conducted using the analytical-interactive model. The results showed that (1) the effort of the local administrators of Banyumulek Village was done through the Women’s Cooperative of Pottery Craftsmen (KOPWAN) with their various working programs, and the forms and strategies of economic empowerment for the tourism-based community in Banyumulek Village included (a) socialization and counseling, (b) training/workshop, (c) cooperation with tourism entrepreneurs, (d) accommodating pottery craftsmen and vendors, and (e) empowerment for pottery craftswomen, (2) some of the achievements or impacts of tourism-based community empowerment conducted by KOPWAN were (a) employment opportunities, (b) improvement in community’s skills, (c) progress in community’s attitude and courtesy, and (d) use of local customs as a tourism attraction.